THE TRANSFORMATION OF JAKE SULLY: EXPLORING PERSONALITY TRAITS IN THE WORLD OF AVATAR - Fitriacianingtyas, Eva Alfiona; Murtiningrum, Afina (Jurnal Ilmiah Penelitian Mahasiswa, 2024)
This essay examines the personality traits of Jake Sully, the major character in James Cameron's film Avatar (2009), using the Big Five personality traits model. Jake Sully undergoes a profound transformation from a soldier to a key leader among the Na'vi people on the alien moon Pandora. The method used in this research was descriptive qualitative. Two types of data were used in this study, namely primary and secondary. Primary data were taken from the movie. Meanwhile, secondary data were taken from e-books, e-journals, and articles about personality traits and social interaction. There were several steps to analyze the data, such as watching the movie and reading the script of Avatar (2009), identifying data, classifying data, and reducing data. The result can be drawn from this study is that this transformation is significantly influenced by his personality traits, particularly his Openness to Experience, Extraversion, Conscientiousness and Agreeableness. Jake's high Openness drives his willingness to immerse himself in the Na'vi culture, leading to his eventual rejection of his initial mission and alignment with the indigenous people. His Extraversion, marked by sociability and assertiveness, facilitates his integration into the Na'vi community and his rise as a leader during the conflict against human invaders. His growing Conscientiousness reflects a deepening sense of moral responsibility and dedication to the Na'vi cause. Finally, Jake’s agreeableness is evident in his growing empathy and understanding towards the Na'vi. From the beginning of his interactions with the Na'vi, Jake shows a willingness to listen, learn, and respect their ways, even when they differ significantly from his own experiences and beliefs as a soldier. Overall, by analyzing Jake Sully's character development through these personality traits, the essay highlights the narrative storyline and thematic depth in storytelling.Keywords: personality traits, openness to experience, extraversion, conscientiousness, agreeableness